Advances in mRNA-Based Cancer Vaccines - Ling Ni (Vaccines, 2023)
Cancer is a leading cause of death worldwide, accounting for millions of deaths every year. Immunotherapy is a groundbreaking approach for treating cancer through harnessing the power of the immune system to target and eliminate cancer cells. Cancer vaccines, one immunotherapy approach, have shown promise in preclinical settings, but researchers have struggled to reproduce these results in clinical settings. However, with the maturity of mRNA technology and its success in tackling the recent coronavirus disease 2019 (COVID-19) pandemic, cancer vaccines are expected to regain attention. In this review, we focused on the recent progress made in mRNA-based cancer vaccines over the past five years. The mechanism of action of mRNA vaccines, advancements in neoantigen discovery, adjuvant identification, and delivery materials are summarized and reviewed. In addition, we also provide a detailed overview of current clinical trials involving mRNA cancer vaccines. Lastly, we offer an insight into future considerations for the application of mRNA vaccines in cancer immunotherapy. This review will help researchers to understand the advances in mRNA-based cancer vaccines and explore new dimensions for potential immunotherapy approaches.